Genotoxicity of TiO2 Nanoparticles in Four Different Human Cell Lines (A549, HEPG2, A172 and SH-SY5Y) - Brandão, Fátima (2021)
This article belongs to the Special Issue Toxicity and Ecotoxicity Assessment of Nanomaterials by In Vitro Models